STUDI EKSPERIMEN KETAHANAN SHEET METAL YANG DILAPISI FIBERGLASS CSM 300 TERHADAP KONDISI LINGKUNGAN - Aan Prayuda (2022)
Weather conditions where Indonesia has a tropical climate, extreme weather conditions, Tropical climates are changes in temperature or weather that occur very often. This has an impact on the easy occurrence of the corrosion rate phase on the tank wall which results in corrosion of the sheet metal. Fiberglass CSM 300 is a material derived from glass fiber in the form of a fluid (liquid) so that it becomes an irregular thin fiber with a density of 300 g/m2 which has many uses such as wall coating, tank lining, and others.resin Yukalac 157 is a type of resin that is very suitable to be coated using the hand lay up and spray up molding methods. The object of this research is the fiberglass type CSM 300 using yukalac 157 polyester resin wall surface sheet metal which is influenced by external factors such as changes in temperature, solar radiation, and humidity in the environment which can cause moss on the sheet metal which has an effect on on the corrosion rate of the sheet metal .surface layer fiberglass has effective resistance to direct sunlight and rainwater, as well as significant changes in environmental temperature, as evidenced by the absence of high corrosion on the test material, the results of the moisture test of the test material moisture test material.layer fiberglass has resistance to moisture so that it cannot be overgrown with moss on the layer so that it is not overgrown with moss on the surface layer of the fiberglass .